User Interface Design of Banyumas Wayang Museum Introduction Using Design Thinking - Subianto, Tegar; Astuti, Tri; Arifudin, Dani (Program Studi Teknik Informatika Universitas Pamulang, 2024)
This research was carried out because of the importance of introducing the Banyumas Wayang Museum to add insight and introduce the existence of the museum, considering that there are still many who do not know about it. This application is expected to be an effective medium for education and preservation of local culture. To solve this problem, the research involves potential users of the application and the creation of interface design is carried out based on five stages of Design Thinking, namely Empathy, Define, Ideate, Prototype, and Testing. The result of this research is the design of the User Interface of the Banyumas Wayang Museum introduction application made using the Figma application. The trial stage was carried out to test the feasibility of the design that had been made using the System Usability Scale method and obtained a score of 77.75 with a grade of B, which means that this design was successfully made and can be continued to the application system development stage. This score shows that this design has met the standards of comfort and ease of use for potential users. This research is expected to make a real contribution to efforts to preserve local culture and promote the Banyumas Wayang Museum more widely, for the results obtained conclude that this research is completed and the design can be deployed into a system.